Evolution of Economic and Social of “Ruea Nuea” in Khiri Wong Community of Lan Saka District, Nakhon Si Thammarat Province, Thailand - Khaenamkhaew, Daycho; Muhamud, Chettha (Community and Social Development Journal, 2023)
This research brought together the issues of economic and social identity of the Khiriwong community with information about the lives of the people in this community to link to the creation of shared values of innovation through the use of the disappearance of the Ruea Nuea over time, wants to highlight the identity and evolution of Ruea Nuea, and tries to present the relationship based on the way of subsistence production in the past through stories that show the importance. This research aims to study the Economic and Social Evolution of “Ruea Nuea” in the Khiri Wong Community of Lan Saka District, Nakhon Si Thammarat Province. This qualitative research included 16 key informants, namely elderly people and village sages who knew about Ruea Nuea in the Khiri Wong Community. This study focuses on participant observation by organizing the group conversation process. It uses structured interviews and opens community forums for data processing and analysis to connect issues. It synthesizes the descriptive analysis and presents the narrative study results of the community. The results showed that the Economic and Social Evolution of Ruea Nuea, consisted of: The era of prosperity in subsistence production. Ruea Nuea was a tool for the occupation with the social and economic lifestyle and the relationship system of people in the Khiriwong community. It is considered a range of "Subsistence production", and living a self-sufficient life. The transition era of marketing relationship production happened in this period. Convenient transportation and connection to the economic progress of the community. “The market system is integrated with the livelihood”, which led to the decline of the ship's role in Ruea Nuea, leading to conservation, and the recession and conservation through traditions and rituals of Ruea Nuea from the old to the new generation in the Kiriwong community. This leads to participation in the conservation of Ruea Nuea. It indicates that Ruea Nuea is important for the coordinating treatment, and create value for the local culture.